Incidências de manifestações patológicas causadas por construções nas edificações vizinhas no município de Vitória - ES - Pinho, Giusilene Costa de Souza (2012)
The population growth of cities results in the use and occupation of intensive urban space, thus causing large high density. During construction or reconstruction of buildings, especially works of multiple floors, complaints occur from owners of neighboring buildings, who are hit by the effects work nearby. These occurrences can turn into pathological manifestations in pre-existing surrounding buildings. The purpose of this study is to detect the incidence of injuries and pathologies through a survey of cases with reports of inspections in Vitória - ES, as well as conducting qualitative and quantitative study of diseases manifested in these buildings, resulting in constructions surrounding. It is characterized as having the document research method as incidence methodology. The results presented are: four neighborhoods, Jardim da Penha, Jardim Camburi, Praia do Canto and Santa Luiza, totaling 56.67% of the total cases studied; the year with the highest number of reports was 2007; the nature of the buildings affected, 49.09% are single family; the nature of the works causing, 58.55% are multifamily buildings; the legality of causing works, 66.66% were licensed by the Municipality; the type of pathological manifestation, which presented a higher rate was the fissure, with 47.97% of the cases researched; pathologies surveyed, 68.46% came during the foundation; the foundation phase which generated higher incidence of diseases was the period of stakes insertion, with 31.57% of cases. It is concluded that the laws must be improved to prevent or even, at first, to minimize these occurrences.